Post-Transcriptional Regulation of Gene Expression in Yersinia Species - Schiano, Chelsea A.; Lathem, Wyndham W. (Frontiers in Cellular and Infection Microbiology, 2012)
Proper regulation of gene expression is required by bacterial pathogens to respond to continually changing environmental conditions and the host response during the infectious process. While transcriptional regulation is perhaps the most well understood form of controlling gene expression, recent studies have demonstrated the importance of post-transcriptional mechanisms of gene regulation that allow for more refined management of the bacterial response to host conditions. Yersinia species of bacteria are known to use various forms of post-transcriptional regulation for control of many virulence-associated genes. These include regulation by cis- and trans-acting small non-coding RNAs, RNA-binding proteins, RNases, and thermoswitches. The effects of these and other regulatory mechanisms on Yersinia physiology can be profound and have been shown to influence type III secretion, motility, biofilm formation, host cell invasion, intracellular survival and replication, and more. In this review, we will discuss these and other post-transcriptional mechanisms and their influence on virulence gene regulation, with a particular emphasis on how these processes influence the virulence of Yersinia in the host.